2021
DOI: 10.1111/ijcp.14899
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatosteatosis in HBsAg seroconversion in HBeAg‐negative chronic hepatitis B patients

Abstract: Hepatitis B virus (HBV) infection is the most common viral infectionin the world, and more than 350 million chronic carriers are estimated. 1 The persistence of hepatitis B surface antigen (HBsAg) for more than 6 months is defined as chronic infection. 2 In patients with chronic HBV infection, the annual HBsAg seroclearence is around 0.5%-1%. 2,3 In chronic HBV infection, some individual and viral characteristics such as advanced age, presence of hepatic steatosis (HS), normal ALT levels, negative HBeAg and HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…On the other hand, several large studies with long-term follow-up have reported a lower risk of HCC among CHB-FL patients compared to CHB-no FL patients [ 12 , 13 ]. Similar contradictory findings have also been observed in risk of cirrhosis [ 14 ], hepatic decompensation [ 8 , 15 , 16 ], mortality [ 7 - 9 , 13 - 19 ] as well as in the incidence of HBsAg seroclearance [ 20 - 26 ]. These findings are intriguing as one would expect the co-existence of two chronic liver diseases to result in worse outcomes, yet there are laboratory and clinical data suggesting the potential protective effects of FL in CHB patients [ 27 - 29 ].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…On the other hand, several large studies with long-term follow-up have reported a lower risk of HCC among CHB-FL patients compared to CHB-no FL patients [ 12 , 13 ]. Similar contradictory findings have also been observed in risk of cirrhosis [ 14 ], hepatic decompensation [ 8 , 15 , 16 ], mortality [ 7 - 9 , 13 - 19 ] as well as in the incidence of HBsAg seroclearance [ 20 - 26 ]. These findings are intriguing as one would expect the co-existence of two chronic liver diseases to result in worse outcomes, yet there are laboratory and clinical data suggesting the potential protective effects of FL in CHB patients [ 27 - 29 ].…”
Section: Introductionsupporting
confidence: 58%
“…1 ). Our manual search of bibliographies of relevant articles provided eight additional potential studies [ 11 , 13 , 16 , 19 , 20 - 22 , 26 ]. In total, 19 studies involving 17,955 patients (6,047 CHB-FL, 11,908 CHB-no FL) met our inclusion criteria were included in the conventional MA [ 5 - 16 , 18 , 20 - 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and screening the titles and abstracts, 135 potentially available studies were identified. Of these, 34 eligible studies7–10,13–42 were included for analysis at the final stage.…”
Section: Resultsmentioning
confidence: 99%
“…A cohort study of 2385 HBsAg-positive Taiwanese civil servants (91.8% of patients not receiving antiviral therapy) followed 35,603.1 person-years, and 628 individuals achieved HBsAg clearance, which found that HS may have promoted HBsAg clearance (sub-distribution hazard ratio = 1.27, 95%CI 1.07–1.50) [ 30 ]. The Turkish study also showed that HS was an independent predictor of spontaneous HBsAg seroconversion in hepatitis B e antigen (HBeAg)-negative CHB patients (OR = 2.07, P = 0.03), and patients with mild HS were easy to achieve HBsAg seroconversion [ 31 ].…”
Section: Interaction Between Hbv Infection and Nafldmentioning
confidence: 99%